2002
DOI: 10.1016/s0035-9203(02)90249-x
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania (Viannia) spp. dissemination and tissue tropism in naturally infected dogs (Canis familiaris)

Abstract: First evidence is presented for Leishmania (Viannia) spp. dissemination and tissue tropism in the domestic dog. Using PCR and histology, parasites were detected in the conjunctiva, lung, lymph nodes and ovaries of 2 naturally infected Peruvian dogs. The detection of parasites in the blood indicates that parasite dissemination to those organs may have been haematogenous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
1
10
1
3
Order By: Relevance
“…Amastigotes can reach the ocular region via the bloodstream (Reithinger et al, 2002) and most likely also via the lymphatic tissue of the conjunctiva (Strauss-Ayali et al, 2004). According to our results, in all dogs Leishmania kDNA was detected in CS on D360, though parasite loads were lower than those observed in OS and VS. Low parasite loads in the conjunctiva have been described by others (Ferreira et al, 2013;Lombardo et al, 2012) and it is thought that amastigotes reach the conjunctival epithelium and persist in a small number of infiltrating macrophages (StraussAyali et al, 2004).…”
Section: Dogsupporting
confidence: 55%
“…Amastigotes can reach the ocular region via the bloodstream (Reithinger et al, 2002) and most likely also via the lymphatic tissue of the conjunctiva (Strauss-Ayali et al, 2004). According to our results, in all dogs Leishmania kDNA was detected in CS on D360, though parasite loads were lower than those observed in OS and VS. Low parasite loads in the conjunctiva have been described by others (Ferreira et al, 2013;Lombardo et al, 2012) and it is thought that amastigotes reach the conjunctival epithelium and persist in a small number of infiltrating macrophages (StraussAyali et al, 2004).…”
Section: Dogsupporting
confidence: 55%
“…Even though this investigation did not detect Leishmania or the DNA of L. (Viannia) in the blood and bone marrow of the dogs, even in the two animals that had lesions, there are reports of the presence of Leishmania DNA in the blood 13,14,19,32,33 and bone marrow 14,32 of dogs in ACL-endemic areas. Previously, Velásquez et al 19 found, in the same area of study, the DNA of L.…”
Section: Discussioncontrasting
confidence: 55%
“…Considering that amastigotes within macrophages can reach the mucosae through the lymphatic and/or hematogenous route [32] nasal tissues are susceptible to parasite colonization owing to the large number of blood vessels in the mucosa. Furthermore, the muzzle is a favorable site for sand fly bites due to the absence of hair.…”
Section: Discussionmentioning
confidence: 99%